A 'golden' SNP in CmOr governs the fruit flesh color of melon (Cucumis melo). (April 2015) - Tzuri, Galil; Zhou, Xiangjun; Chayut, Noam; Yuan, Hui; Portnoy, Vitaly; Meir, Ayala; Sa'ar, Uzi; Baumkoler, Fabian; Mazourek, Michael; Lewinsohn, Efraim; Fei, Zhangjun; Schaffer, Arthur A.; et al.
Summary The flesh color of Cucumis melo (melon) is genetically determined, and can be white, light green or orange, with β–carotene being the predominant pigment. We associated carotenoid accumulation in melon fruit flesh with polymorphism within CmOr, a homolog of the cauliflower BoOr gene, and identified CmOr as the previously described gf locus in melon. CmOr was found to co‐segregate with fruit flesh color, and presented two haplotypes (alleles) in a broad germplasm collection, one being associated with orange flesh and the second being associated with either white or green flesh. Allelic variation of CmOr does not affect its transcription or protein level. The variation also does not affect its plastid subcellular localization. Among the identified single nucleotide polymorphisms (SNPs) between CmOr alleles in orange versus green/white‐flesh fruit, a single SNP causes a change of an evolutionarily highly conserved arginine to histidine in the CmOr protein. Functional analysis of CmOr haplotypes in an Arabidopsis callus system confirmed the ability of the CmOr orange haplotype to induce β–carotene accumulation. Site‐directed mutagenesis of the CmOr green/white haplotype to change the CmOR arginine to histidine triggered β–carotene accumulation. The identification of the 'golden' SNP in CmOr, which is responsible for the non‐orange and orange melon fruit phenotypes, provides new tools for studying the Or mechanism of action, and suggests genome editing of the Or gene for nutritional biofortification of crops.